Pelatihan Penggunaan Software Geogebra dalam Memecahkan Soal Geometri Ruang Berbasis Contextual Teaching and Learning - Hafizah Delyana; Radhya Yusri; Ainil Mardiyah; Istikhfar Istikhfar; Eva Pebri Ningsih (LPPM Universitas Bumigora, 2022)
The utilization of technology applications in classroom learning is limited to the use of power points. The use of PowerPoint media, especially in three-dimensional material, has a less attractive presentation. Graphic representations and three-dimensional images in the learning process are mostly still made manually. Training on the use of Geogebra software for mathematics teachers is one solution to overcome the problems that occur to increase the knowledge and skills of teachers in designing and making three-dimensional images. The training is held for three months once a week. The training was carried out using a guidance method that aims to train teachers of SMA Negeri 2 Padang to be able to create three-dimensional images by utilizing Geogebra software and be able to apply them in the learning process. The results obtained in this activity are all teachers who participate in this activity can use Geogebra software in learning mathematics. The use of Geogebra software can overcome existing problems so that its use can help students understand abstract material concepts. Students are also able to explore, and conduct investigations and searches using Geogebra software and can test more examples in a short time rather than just using the manual method. Students can also find, construct, conclude and finally understand how to describe the shape of space correctly.